Goldfinch - Kennedy, Raven (Kennedy, Raven. Plated prisoner series, 2024)
"Slade and I are connected by more than just fated magic, and we will always find each other. The Stone King is trying to destroy me, but what he hasn't realized is this: Gold bends, but stone breaks. And a Goldfinch does not fall. It flies." -- Amazon.com